Influence of the environmental factors on the intensity of the oxygen, ammonium, and phosphate metabolism in the agar-containing seaweed Ahnfeltia tobuchiensis (Ahnfeltiales, Rhodophyta). - Cherbadgy, I I; Sabitova, L I (PANGAEA, 2011)
A complex study of influence of various environmental factors on rates of oxygen (M_O2 ), ammonium (M_NH4), and phosphate (M_PO4) metabolism in Ahnfeltia tobuchiensis has been carried out in situ in the Izmena Bay of the Kunashir Island. The following environmental factors have been included into the investigation: photosynthetically active radiation (PAR); ammonium (NH4); phosphate (PO4); and contents of carbon (C), nitrogen (N), phosphorus (P), and chlorophyll a (Chl) in tissue. Population of agar-containing seaweed A. tobuchiensis forms a layer with thickness up to 0.5 m, which occupies about 23.3 km**2; biomass is equal to 125000 tons. Quantitative assessment of organic matter production and nutrient consumption during oxygen metabolism has been carried out for the whole population. It has been shown that daily oxygen metabolism depends on PAR intensity, concentrations of PO4 and NH4 in seawater, and contents of N and P in tissues (r**2=0.78, p<0.001). Average daily NH4 consumption is 0.21 µmol/g of dry weight/hour and depends on NH4 and O2 concentrations in seawater and on ? and Chl a contents in algal tissues (r**2=0.64, p<0.001). Average daily PO4 consumption is 0.01 µmol/g of dry weight/hour and depends on NH4 concentrations in seawater and on P contents in algal tissues (r**2=0.40, p<0.001).
(Table 2) Contents of chlorophyll a, organic carbon, nitrogen, and phosphorus and their molar ratios in dried matter of Ahnfeltia tobuchiensis agar containing seaweed from the Izmena Bay, Kunashir Island (South Kurils)
Keywords: Archive of Ocean Data; ARCOD; Carbon, organic, total; Carbon/Nitrogen ratio; Carbon/Phosphorus ratio; Chlorophyll a per unit sediment mass; Date/Time of event; Date/Time of event 2; Izmena_Bay-04-1; Izmena_Bay-04-2; Izmena_Bay-04-3; Izmena_Bay-04-4; Izmena_Bay-04-5; Izmena_Bay-04-6; Izmena Bay, Kunashir Island; MULT; Nitrogen, total; Nitrogen/Phosphorus ratio; Phosphorus; Spectrophotometry; Wet combustion